Validation of a picture book to be used in a pan-European dietary survey. Issue 9 (1st February 2018) - Vilela, Sofia; Lopes, Carla; Guiomar, Sofia; Severo, Milton; Rangelova, Lalka; Petrova, Stefka; Horváth, Zuszsanna; Cseh, Júlia; Schweter, Antje; Lindtner, Oliver; Ambrus, Árpád; Torres, Duarte
Abstract: Objective: To validate a picture book for estimation of food portion sizes using two approaches: (i) 'perception' of food portions by comparison with a series of food photos; and (ii) 'conceptualization and memory', using the same photos to estimate the amount of served food one hour after self-served food portions. Design: Each partner developed a country-specific picture book based on the so-called EPIC-Soft picture book. Representative and common photo series were chosen achieving approximately 25 % of the original picture book ( n 23). Three portions from each photo series were randomly selected. Setting: The study was performed within the Pilot study in the view of a Pan-European dietary survey – Adolescents, adults and elderly (PILOT-PANEU) project. Subjects: A sample of adolescents and adults was recruited in five countries: Bulgaria ( n 103), Finland ( n 34), Germany ( n 69), Hungary ( n 62) and Portugal ( n 77). Results: Among the portions of the corresponding photo series and depending on the type of food, from 18 % (cheese) to 96 % (ratatouille) of participants chose the correct portions. In the perception study, agreement between the portions shown and reported was substantial (intraclass correlation coefficient (ICC)=0·805) and the mean difference was very low. In the memory study, agreement between the served and reported portions was lower than in the perception study (ICC=0·536). Agreement also seemed to decrease as the appearance of food on the plate differed from food in the picture. Conclusions: Overall, the picture series selected can be applied in future intake surveys to quantify foods similar to those depicted in the pictures.